EORTC QLQ C-30 Quality of Life Assessment in Breast Cancer Patients Undergoing Chemotherapy at Mohammad Hoesin Hospital, Palembang. - Plorinda, Vanesha; Qodir, Nur; Liberty, Iche Andriyani; Umar, Mulawan; Ikhsan, Diyaz Syauki (Indonesian Journal of Cancer, 2025)
Background: Breast cancer has a high prevalence in Indonesia, with many patients undergoing chemotherapy that impacts their daily lives. Measuring quality of life (QoL) is essential to capture physical, emotional, and social challenges, and the EORTC QLQ-C30 provides a validated tool for this purpose. This study aimed to assess the QoL of breast cancer patients undergoing chemotherapy at RS Mohammad Hoesin Palembang. Methods: This study used a descriptive observational method with a cross-sectional approach. The sample consisted of 106 breast cancer patients undergoing chemotherapy at RS Mohammad Hoesin Palembang, with inclusion criteria of patients ≥ 18 years undergoing chemotherapy and exclusion of those with severe comorbidities or cognitive impairment. Data were collected through interviews using the EORTC QLQ-C30 questionnaire.Results: The study assessed the quality of life of breast cancer patients undergoing chemotherapy at RS Mohammad Hoesin Palembang using the EORTC QLQ-C30. The results showed that the average functional scale score was 78.6 ± 5.85, with the highest in emotional function (84.98 ± 9.27) and the lowest in role function (72.33 ± 18.77). On the symptom scale, the mean score was 57.88 ± 13.91, with constipation being the most reported symptom (74.75 ± 19.14), while insomnia and decreased appetite were the least reported (37.81 ± 11.90). The overall health status score averaged 77.56 ± 11.92. The highlight of this study is that although emotional functioning is relatively well-preserved, role limitations and physical symptoms, particularly constipation, substantially affect patients’ quality of life, underscoring the need for supportive care strategies during chemotherapyConclusions: The quality of life of breast cancer patients undergoing chemotherapy, based on the EORTC QLQ-C30 results, indicates that the functional scale is better than the symptom scale and general health status. Routine and comprehensive quality of life assessments are essential for understanding the impact of treatment and improving the clinical management of patients.